Teacher Suggestion Feedback Facilitates Creativity of Students in STEAM Education - Shen, Sha; Wang, Saidi; Qi, Yun; Wang, Yanli; Yan, Xiangdong (Frontiers in Psychology, 2021)
This study examined the influence of teachers' formative feedback types on creativity in STEAM education. Participants were 60 undergraduate students who randomly assigned to the teacher opinions feedback group and the teacher suggestion feedback group, and took part in three courses STEAM education of 3D printing technology. Before and after each course, they were asked to fill out the Eugene Creativity Test. The results showed that compare with teacher opinions feedback group, the participants in teacher suggestion feedback group showed higher score on the creativity scale. This suggests that teacher suggestion feedback can be useful for improving the creativity in STEAM education.